The record as artwork : From futurism to conceptual art : the collection of Germano Celant. - Celant, Germano; Livet, Anne; The Fort Worth Art Museum, Fort Worth; Moore College of Art Gallery, Philadelphia; Musée d'art contemporain, Montréal; Museum of Contemporary Art, Chicago (Fort Worth : Fort Worth Art Museum Fort Worth, 1977)
Wilhite, Bob ; Goldstein, Jack ; Russolo, Luigi ; Marinetti, Filippo Tommaso ; Depero, Francesco ; Schwitters, Kurt ; Duchamp, Marcel ; Ball, Hugo ; Dubuffet, Jean ; Klein, Yves ; Wilp, Charles ; Chopin, Henri ; Hausmann, Raoul ; Ben ; Tinguely, Jean ; Kopcke, Addi ; Kaprow, Allan ; Kluver, Billy ; van der Marck, Jan ; Weiner, Lawrence ; Schraenen, Guy ; Radigue, Eliane ; Nannucci, Maurizio ; Totino, Arrigo Lora ; Heidsieck, Bernard ; Dibbets, Jan ; Beuys, Joseph ; Christiansen, Henning ; Struycken, Peter ; Raijmakers, Dick ; Bruynel, Ton ; Ruthenbeck, Reiner ; Sarkis ; Snow, Michael ; Dias, Antonio ; Dimitrijevic, Braco ; Allen, Terry ; Topor, Roland ; Goldstein, Jack ; Davie, Alan ; The Artists' Jazz Band ; Art & Language ; Brus, Günter ; Nitsch, Hermann ; Roth, Dieter ; Rühm, Gerhard
biog. Germano Celant p. 110-111
discogr. p. 96-107
record producers p. 108-109
Engels
Frans
The record as artwork : From futurism to conceptual art : the collection of Germano Celant, The Fort Worth Art Museum, Fort Worth, December 4, 1977 - January 15, 1978 / Moore College of Art Gallery, Philadelphia, February 3 - March 8, 1978 / Musee d'Art Contemporain, Montreal, September 7 - October 22, 1978 / Museum of Contemporary Art, Chicago, 1979